Preparation method of transparent ABS (Acrylonitrile Butadiene Styrene) grafted latex
By using the three-stage method of adding activator after high-speed swelling at low temperature, transparent ABS graft latex was prepared, which solved the problems of poor emulsion stability and low production efficiency caused by MMA hydrolysis in the prior art, and achieved transparent ABS graft latex with high solids content, high stability and excellent optical performance.
Patent Information
- Application Number
- CN202510002888.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
AI Technical Summary
The existing preparation methods for transparent ABS need to introduce MMA when adjusting the refractive index, resulting in MMA hydrolysis, and the pH of the emulsion is greatly reduced, resulting in poor grafting effect, poor emulsion stability, low production efficiency, poor performance and a lot of waste during the process.
Transparent ABS grafted latex is prepared by adding three-stage activator after high-speed swelling, and graft polymerization is carried out at low temperature. The inner graft structure is formed through swelling technology to improve the stability and solid content of the latex.
It realizes efficient preparation of high-solid content transparent ABS grafted latex at low temperatures, improving the stability and optical performance of the latex, reducing production costs and waste generation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics ABS, and particularly relates to a method for preparing transparent ABS grafted rubber powder. Background Art
[0002] ABS is a copolymer of acrylonitrile-butadiene-styrene. It is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. It has good formability and is mainly used for alloys and plastics.
[0003] Transparent ABS is made by adjusting the refractive index of the continuous phase MSAN and the rubber phase powder so that the difference between the two phases is less than 0.005, so as to achieve the effect of transparency under visible light. Due to its good impact resistance, wear resistance and chemical resistance, transparent ABS is widely used in transparent materials. However, since MMA needs to be introduced in the process of adjusting the refractive index, at the grafting temperature of 60-80°C, MMA will be hydrolyzed and the pH of the emulsion will be greatly reduced, resulting in poor grafting effect and poor emulsion stability. The solid content of the grafted emulsion needs to be reduced to ensure stability. The prepared transparent ABS products often have low production efficiency, poor performance and a lot of waste in the process.
[0004] In patent CN1177876C, in order to improve the stability of latex, a large amount of sulfonate is added to maintain the balance of the emulsion under pH fluctuations, but the solid content of the latex is low, and a large amount of electrolytes are introduced in the process, resulting in an increase in wastewater during the production process, and residual impurities make the product haze and B value high.
[0005] In patent CN105008406A, a polymerizable emulsifier is used in the grafting process to improve product stability. However, the cost of the polymerizable emulsifier is relatively high, and the emulsifier will remain in the polymer, affecting the light transmittance and mechanical properties of the product.
[0006] Therefore, providing a method for preparing a transparent ABS graft latex with a simple synthesis method, low polymerization temperature, good emulsion stability, high solid content and excellent optical properties, and using it for transparent ABS with high light transmittance and low haze performance has become the focus of current research. Summary of the invention
[0007] The invention provides a method for preparing a transparent ABS graft latex, which can be carried out at low temperature and is prepared by a method of adding an activator in three stages after high-speed swelling. The latex has high stability and can be used to produce a graft latex with high solid content and has excellent optical properties.
[0008] In order to achieve the above invention object, the present invention is implemented by the following technical solutions:
[0009] A method for preparing a transparent ABS graft latex comprises the following steps:
[0010] (1) Add polybutadiene latex (PB latex), comonomer 1, emulsifier and water into a reactor and mix them evenly;
[0011] (2) adding the first portion of the activator at the reaction temperature, stirring, fully dispersing the activator into the reaction solution, and swelling for 0.5-1h;
[0012] (3) adding comonomer 2, oxidant, and the second activator into the reactor within 1-5 hours to react;
[0013] (4) After the third step reaction is completed, a third portion of activator is added and the reaction is continued for 1-4 hours to obtain ABS grafted latex;
[0014] Optionally, (5) adding water and a coagulant into a reactor, adding the ABS grafted latex prepared in step (4) into the coagulant solution, reacting, and then filtering, washing, and drying to obtain a grafted rubber powder;
[0015] In step (1), the emulsifier is one or more of potassium oleate, potassium fatty acid, potassium rosinate, and sodium dodecyl sulfate, preferably potassium oleate, and the dry basis mass ratio of the emulsifier to the polybutadiene latex is 0.01:1-0.08:1, preferably 0.03:1-0.05:1.
[0016] Preferably, the comonomers include MMA, polyethylene and acrylonitrile. Based on the total mass of the mixed monomers as 100 parts, MMA is 50-80 parts, preferably 60-70 parts, styrene is 10-35 parts, preferably 15-20 parts, acrylonitrile is 5-15 parts, preferably 10-12 parts, and the mass ratio of comonomer 1 to polybutadiene latex is 0.1-0.4, preferably 0.2-0.3.
[0017] In step (2), the first activator includes a first reducing agent, a first auxiliary reducing agent and a first complexing agent, wherein the first reducing agent includes one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the first auxiliary reducing agent includes one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the first complexing agent includes one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably EDTA-2 sodium.
[0018] Among them, in the first activator, the dry weight ratio of the first reducing agent to the polybutadiene latex is 10 -6 -10 -3 : 1, preferably 10 -5 -10 -4: 1, the dry basis mass ratio of the first reducing agent to the polybutadiene latex is 0.0001-0.01: 1, preferably 0.001-0.005: 1, the dry basis mass ratio of the first complexing agent to the polybutadiene latex is 0.0002-0.02: 1, preferably 0.002-0.01: 1,
[0019] Step (2) is a high-speed swelling stage, and the stirring linear speed is 0.5 m / s-5 m / s, preferably 1 m / s-3 m / s.
[0020] In step (3), comonomer 2 includes MMA, styrene and acrylonitrile. Based on the total mass of comonomer 2 being 100 parts, the mass of MMA is 50-80 parts, preferably 60-70 parts, the mass of styrene is 10-35 parts, preferably 15-20 parts, the mass of acrylonitrile is 5-15 parts, preferably 10-12 parts, and the mass ratio of comonomer 2 to polybutadiene latex is 0.5-1, preferably 0.6-0.8.
[0021] In step (3), the oxidant is a peroxide, preferably one or more of cumene hydroperoxide, diisopropylbenzene hydroperoxide, and tert-butyl hydroperoxide, more preferably cumene hydroperoxide, and the mass ratio of the oxidant to the dry PB basis is 0.0001:1-0.01:1, preferably 0.02:1-0.05:1.
[0022] In step (3), the second activator includes a second reducing agent, a second auxiliary reducing agent and a second complexing agent, wherein the second reducing agent includes one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the second auxiliary reducing agent includes one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the second complexing agent includes one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably EDTA-2 sodium.
[0023] Preferably, the mass ratio of the second reducing agent, the second auxiliary reducing agent and the second complexing agent is: 0.001-1: 0.1-10: 0.2-20, preferably 0.01-0.1: 1-5: 2-10.
[0024] In step (3), the amount of the second activator is 10%-30% of the mass of the first activator, preferably 15%-25%, the reaction temperature is 5-50°C, preferably 10-40°C, and the reaction time is 1-5h, preferably 2-4h.
[0025] In step (4), the third activator includes a third reducing agent, a third auxiliary reducing agent and a third complexing agent, wherein the third reducing agent includes one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the third auxiliary reducing agent includes one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the third complexing agent includes one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably disodium EDTA.
[0026] Preferably, the mass ratio of the third reducing agent, the third auxiliary reducing agent and the third complexing agent is: 0.001-1: 0.1-10: 0.2-20, preferably 0.01-0.1: 1-5: 2-10.
[0027] In step (4), the amount of the third activator is 0.4%-10% of the mass of the first activator, preferably 5%-8%, the reaction temperature is 5-50°C, preferably 10-40°C, and the reaction time is 1-4h, preferably 2-3h.
[0028] In step (5), the ABS grafted latex is evenly added into the coagulant solution within 1 hour.
[0029] In step (5), the reaction temperature is 75-95°C.
[0030] In step (5), the coagulant is one or more of sulfuric acid, magnesium sulfate, and calcium chloride, preferably calcium chloride, and the dry basis mass ratio of the coagulant to the latex is 1:100-10:100, preferably 3:100-6:100.
[0031] In the present invention, in steps (1)-(2), under the conditions of low temperature and high-speed stirring, the monomer and the activator quickly enter the rubber interior to swell, forming a large number of reaction sites. In step (3), after the addition of the oxidant, the latex that swells internally reacts quickly to obtain sufficient internal grafting, and the remaining monomers and emulsifiers that are slowly added form a core-shell structure on the outer layer of the rubber. In step (4), the activator is replenished again to further complete the monomer reaction. The internal grafting provides sufficient optical path for the rubber, which can improve the optical properties of the product. At the same time, the swelling of the rubber interior also improves the toughening effect of the rubber, so that the optical properties and mechanical properties of the product are improved.
[0032] The beneficial effects of the present invention are as follows: the method for preparing the rubber powder of the present invention can carry out graft polymerization at a relatively low temperature, which can reduce costs on the one hand, and reduce the pH reduction caused by the hydrolysis of MMA on the other hand, thereby improving the stability of the latex, making the solid content of the latex reach more than 50%, and the swelling effect can improve the product performance. DETAILED DESCRIPTION
[0033] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0034] Analytical instruments:
[0035] Izod impact strength: CEAST 9050 pendulum impact tester
[0036] Transmittance / Haze: Hazegard 1 Transmittance and Haze Meter
[0037] Tensile strength, elongation at break: Instron 5966 universal materials testing machine
[0038] Test method:
[0039] Izod impact strength: Standard ASTM D256
[0040] Tensile strength, elongation at break: standard ASTM D638
[0041] Transmittance / Haze: ASTM D1003
[0042] Grafting rate test:
[0043] (1) Weigh the dried transparent ABS powder (water content less than 1%, accurate to 0.0001 g, mass is G) into a 100 ml flask, add 50 ml of acetone along the neck of the flask, install a condenser on the flask, and reflux in a 65°C constant temperature water bath for 2.0 hours. During this period, do not let the water bath temperature exceed 65°C, otherwise violent boiling may occur.
[0044] (2) Remove the flask and cool it to room temperature. Transfer the solution in the flask to a weighed beaker, let it settle for 4 hours, and remove the supernatant. Place the beaker in a vacuum oven and dry it under vacuum at 65°C to constant weight. Weigh and calculate the dry basis mass as G1.
[0045] The grafted rubber content X (%) is calculated as follows:
[0046] Grafted rubber content X = G1 / G*100%
[0047] Where: G1—grafted rubber mass (i.e. total of polybutyl acrylate and grafted SAN), unit: g;
[0048] G—sample mass (i.e. ABS grafted powder mass), unit: gram
[0049]
[0050]
[0051] The parts described in Examples 1-5 are molar parts, and the parts described in Examples 6-10 and Comparative Examples are mass parts.
[0052] Slag content test:
[0053] (1) Weigh a certain amount of grafted latex after the reaction is completed, the mass is M;
[0054] (2) The grafted latex is filtered through a 100-mesh filter, the mass of the filter is ma, and after filtration, the filter is rinsed with pure water until the rinse liquid is clear. The filter is dried and weighed, and the mass is recorded as mb. The emulsion residue content is calculated as follows:
[0055]
[0056] Example 1
[0057] (1) Add 100 g of PB and 1 g of potassium oleate on a dry basis into a reactor, adjust the temperature to 20° C., mix well, then add 25 g of a mixed monomer 1 of MMA, SM, and AN (MMA 70 wt%, SM 20 wt%, and AN 10 wt%), stir well, and keep the temperature constant for 0.5 h;
[0058] (2) Add activator-1 (0.01 g ferrous sulfate, 1 g sodium formaldehyde sulfoxylate, 2 g EDTA-2 sodium), adjust the stirring speed to 5 m / s, and stir at high speed for 0.5 h;
[0059] (3) 25 g of mixed monomer-2 of MMA, SM, and AN (MMA 70 wt%, SM 20 wt%, AN 10 wt%), 1 g of oxidant cumene hydroperoxide, and activator-2 (ferrous sulfate 0.001 g, sodium formaldehyde sulfoxylate 0.1 g, EDTA-2 sodium 0.2 g) were uniformly added into the reactor within 1 h, and the reaction was carried out at a constant temperature for 2 h;
[0060] (4) Add activator-3 (0.0001 g of ferrous sulfate, 0.01 g of sodium formaldehyde sulfoxylate, and 0.02 g of sodium EDTA-2) and react at a constant temperature for 1 h;
[0061] (5) Add 1 kg of water and 2.5 g of sulfuric acid into the reactor, raise the temperature to 60°C, and evenly drop the emulsion after the reaction into the coagulant within 1 hour. After the addition is completed, raise the temperature to 80°C and keep it at this temperature for 3 hours. After the reaction is completed, filter, wash, and dry to obtain the grafted rubber powder.
[0062] Embodiment 2-6:
[0063] According to the formula in Table 1, the rubber powders of Examples 2-6 were prepared respectively, and the other reaction conditions and product parameters were the same as those of Example 1. Table 1 shows the raw materials and reaction conditions of Examples 1-6.
[0064] Table 1 Examples 1-6 Raw materials and reaction conditions
[0065]
[0066]
[0067] Comparative Example 1
[0068] A method for preparing transparent ABS, using polybutadiene as the core, grafting MMA-SM-AN polymer, and the reaction temperature is 60-80°C.
[0069] (1) Add 200 parts by mass of polybutadiene latex, 100 parts by mass of water, 1 part by mass of potassium oleate (Qingdao Ruinuo, potassium oleate soap), and 2 parts by mass of initiator potassium persulfate into a reactor and heat it to 50° C.;
[0070] (2) Add 50 parts by weight of mixed monomers (MMA 70wt%, SM 20wt%, AN 10wt%) into the reactor and heat the reactor to 60°C. Add the mixture dropwise for 1 hour. After the addition is completed, keep the mixture at 70°C for 0.5 hour. Stop the reaction after the monomers are consumed.
[0071] Comparative Example 2
[0072] (1) Add 200 parts by mass of polybutadiene latex, 100 parts by mass of water, 3 parts by mass of fatty soap (Qingdao Shuiruocheng fatty acid potassium soap), and 2 parts by mass of sodium persulfate into a reaction kettle, and heat it to 50° C.;
[0073] (2) Add 100 parts by weight of mixed monomers (MMA 50wt%, SM 35wt%, AN 15wt%) into the reactor and heat the reactor to 60°C. Add the monomers dropwise for 1 hour. After the addition is completed, keep the temperature at 80°C for 0.5 hour. Stop the reaction after the monomers are consumed.
[0074] Coagulation and drying: The grafted emulsion prepared in the above example was coagulated by adding 5% dilute sulfuric acid at 70°C, vacuum filtered, and fluidized bed dried (wind speed 180m / s). 3 / h, temperature 70°C, drying time 0.5-1h) to obtain ABS grafted powder.
[0075] Preparation of ABS resin by blending and granulation: The above 24 parts by mass of ABS grafted powder, 76 parts by mass of XT-500 (LG Chemical), 0.1 parts by mass of antioxidant 1010 (BASF, Germany), 0.1 parts by mass of antioxidant 618 (Panhua Chemical (Shanghai) Co., Ltd.), 0.2 parts by mass of magnesium stearate, and 2 parts of N,N-ethylene bisstearamide (Shandong Liang New Materials Co., Ltd.) were kneaded in a high-speed kneader for 5 minutes, and then the mixture was melt-granulated and blended at 220°C in a twin-screw extruder, and granulated to finally obtain ABS resin pellets. The above pellets were dried in an oven at 80°C for 2 hours, and mechanical and optical properties were tested after injection molding.
[0076] In Examples 1-6 and Comparative Examples 1-2, the prepared ABS powder was coagulated and dried, and then blended and granulated to prepare ABS resin for testing. The properties are shown in Table 2:
[0077] Table 2 Performance test results of embodiments and comparative examples
[0078]
[0079] As shown in Table 2, the latex prepared by the method of the present invention in the grafting process can be used to prepare a transparent ABS grafted rubber powder with high stability, high solid content, low slag content, improved production efficiency, and improved performance of the swelling structure, thereby improving the optical properties (light transmittance, haze) of the transparent ABS. This is because, using the preparation method in the patent of the present invention, the transparent ABS can be polymerized at a lower temperature during the grafting process, the MMA hydrolysis is reduced, the latex stability is excellent, the monomer conversion rate is high, the structure is regular, and the swelling technology is used at the same time, the grafting in the product is controllable, the rubber optical path is enlarged, and the toughening effect is improved. The transparent ABS prepared by the ordinary process has MMA hydrolysis at high temperature, low emulsion stability, low grafting rate, and is easily offset by the refraction of rubber particles when light passes through, so the performance deviation.
Claims
1. A method for preparing a transparent ABS graft latex, characterized in that: The following steps are involved: (1) Adding polybutadiene latex, comonomer 1, emulsifier and water into a reactor and mixing them evenly; (2) adding the first portion of the activator at the reaction temperature, stirring, fully dispersing the activator into the reaction solution, and swelling for 0.5-1h; (3) adding comonomer 2, oxidant, and the second activator into the reactor within 1-5 hours to react; (4) After the third step reaction is completed, a third portion of activator is added and the reaction is continued for 1-4 hours to obtain ABS grafted latex; Optionally, (5) water and a coagulant are added to a reactor, and the ABS grafted latex prepared in step (4) is added to the coagulant solution to react, and then filtered, washed, and dried to obtain grafted rubber powder.
2. The preparation method according to claim 1, characterized in that: In step (1), the emulsifier is one or more of potassium oleate, potassium fatty acid, potassium rosinate, and sodium dodecyl sulfate, preferably potassium oleate, and the dry basis mass ratio of the emulsifier to the polybutadiene latex is 0.01:1-0.08:1, preferably 0.03:1-0.05:1; Preferably, the comonomers include MMA, polyethylene and acrylonitrile, and based on 100 parts by total weight of the mixed monomers, MMA is 50-80 parts, preferably 60-70 parts, styrene is 10-35 parts, preferably 15-20 parts, and acrylonitrile is 5-15 parts, preferably 10-12 parts; Preferably, the mass ratio of comonomer 1 to polybutadiene latex is 0.1-0.4, preferably 0.2-0.
3.
3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the first activator includes a first reducing agent, a first auxiliary reducing agent and a first complexing agent, wherein the first reducing agent includes one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the first auxiliary reducing agent includes one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the first complexing agent includes one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably EDTA-2 sodium.
4. The preparation method according to any one of claims 1 to 3, characterized in that In the first activator, the dry weight ratio of the first reducing agent to the polybutadiene latex is 10 -6 -10 -3 : 1, preferably 10 -5 -10 -4 : 1, the dry basis mass ratio of the first auxiliary reducing agent to the polybutadiene latex is 0.0001-0.01: 1, preferably 0.001-0.005: 1, and the dry basis mass ratio of the first complexing agent to the polybutadiene latex is 0.0002-0.02: 1, preferably 0.002-0.01:
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (2) is a high-speed swelling stage, and the stirring linear speed is 0.5 m / s-5 m / s, preferably 1 m / s-3 m / s.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (3), the comonomer 2 includes MMA, styrene and acrylonitrile. Based on the total mass of the comonomer 2 being 100 parts, the mass of MMA is 50-80 parts, preferably 60-70 parts, the mass of styrene is 10-35 parts, preferably 15-20 parts, the mass of acrylonitrile is 5-15 parts, preferably 10-12 parts, and the mass ratio of the comonomer 2 to the polybutadiene latex is 0.5-1, preferably 0.6-0.8; Preferably, in step (3), the oxidant is a peroxide, preferably one or more of cumene hydroperoxide, diisopropylbenzene hydroperoxide, and tert-butyl hydroperoxide, more preferably cumene hydroperoxide, and the mass ratio of the oxidant to the dry PB basis is 0.0001:1-0.01:1, preferably 0.02:1-0.05:1; Preferably, in step (3), the second activator comprises a second reducing agent, a second auxiliary reducing agent and a second complexing agent, wherein the second reducing agent comprises one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the second auxiliary reducing agent comprises one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the second complexing agent comprises one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably 2-sodium EDTA; Preferably, the mass ratio of the second reducing agent, the second auxiliary reducing agent and the second complexing agent is: 0.001-1: 0.1-10: 0.2-20, preferably 0.01-0.1: 1-5: 2-10; Preferably, in step (3), the amount of the second activator is 10%-30% of the mass of the first activator, preferably 15%-25%, the reaction temperature is 5-50°C, preferably 10-40°C, and the reaction time is 1-5h, preferably 2-4h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (4), the third activator includes a third reducing agent, a third auxiliary reducing agent and a third complexing agent, wherein the third reducing agent includes one or more of ferrous sulfate, ferrous sulfide and ferrous hydroxide, preferably ferrous sulfate; the third auxiliary reducing agent includes one or more of glucose, lactose, galactose and sodium formaldehyde sulfoxylate, preferably sodium formaldehyde sulfoxylate; the third complexing agent includes one or more of sodium pyrophosphate, disodium EDTA and tetrasodium EDTA, preferably disodium EDTA; Preferably, the mass ratio of the third reducing agent, the third auxiliary reducing agent and the third complexing agent is: 0.001-1: 0.1-10: 0.2-20, preferably 0.01-0.1: 1-5: 2-10; Preferably, the amount of the third activator in step (4) is 0.4%-10% of the mass of the first activator, preferably 5%-8%, the reaction temperature is 5-50°C, preferably 10-40°C, and the reaction time is 1-4h, preferably 2-3h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (5), the ABS grafted latex is evenly added to the coagulant solution within 1 hour; Preferably, in step (5), the reaction temperature is 75-95°C; Preferably, in step (5), the coagulant is one or more of sulfuric acid, magnesium sulfate, and calcium chloride, preferably calcium chloride, and the dry weight ratio of the coagulant to the latex is 1:100-10:100, preferably 3:100-6:100.
Citation Information
Patent Citations
Transparent ABS resin and transparent ABS resin composition
CN105008406A
Method for preparing acrylonitrile butadiene-styrene (ABS) resin through double peak emulsion grafting
CN102199253A
Polybutadiene grafted copolymer, and preparation method and application thereof
CN111116832A
Preparation method of graft polymer and graft polymer
CN116410408A
Preparation method and application of ABS (Acrylonitrile Butadiene Styrene) grafted latex
CN117567693A
Cited By
ABS (Acrylonitrile Butadiene Styrene) rubber powder, low-haze transparent ABS resin and preparation method thereof
CN121203083A